Antioxidant Activity and Inhibitory Potential of Blueberry Extracts Against Key Enzymes Relevant for Hyperglycemia. Issue 1 (21st January 2015) - Pranprawit, Araya; Heyes, Julian A.; Molan, Abdul L.; Kruger, Marlena C.
Abstract Aqueous extracts of Highbush blueberries grown in New Zealand were investigated for their total phenolic concentration, antioxidant activity and potential to contribute to the dietary management of type II diabetes. There were significant differences (P < 0.05) between blueberry genotypes for these measurements. 'Elliott' had the highest total phenolic concentration (2.24 mg gallic acid equivalent/g frozen berries). Across all eight varieties, 'Burlington' showed the highest antioxidant capacity as determined by ferric reducing antioxidant power (2.52 mg FeSO4 equivalent/g frozen berries) and 2, 2′‐diphenyl‐1‐picrylhydrazyl assay (IC50 = 3.41 mg/mL). Most blueberry extracts inhibited α‐amylase and α‐glucosidase activity in vitro, with 'Bluecrop' and 'Jersey' having the highest inhibitory activity for both enzymes. There were no significant correlations between enzyme inhibitory activities and total phenolic concentration or antioxidant capacities across all genotypes, suggesting that such inhibitory activity was influenced by some particular phytochemicals in blueberries. Of the eight genotypes tested, 'Bluecrop' and 'Burlington' may be potential candidates for early management of hyperglycemia. Practical Applications Blueberries (Vaccinium spp.) are commonly available in New Zealand. In addition, various members of this species have been reported to be used as a traditional medicine for diabetic treatment for many years. In the present study, the ability of New Zealand Highbush blueberries to inhibit carbohydrate hydrolyzing enzymes (α‐amylase and α‐glucosidase) was explored in relationship to their phenolic content and antioxidant activity. All aqueous extracts tested exhibited the capacity to inhibit pancreatic α‐amylase and yeast α‐glucosidase enzymes in vitro and these beneficial effects appear to be due to some specific bioactive compounds in blueberries, in particular glucosylated anthocyanins. Our preliminary observation provides a rationale for further animal and clinical studies of a possible use of blueberry for the management of hyperglycemia.